2018
DOI: 10.1016/j.survophthal.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: a review of risk factors and their clinical significance

Abstract: Retinopathy of prematurity (ROP) is a retinal vasoproliferative disease that affects premature infants. Despite improvements in neonatal care and management guidelines, ROP remains a leading cause of childhood blindness worldwide. Current screening guidelines are primarily based on two risk factors: birth weight and gestational age; however, many investigators have suggested other risk factors, including maternal factors, prenatal and perinatal factors, demographics, medical interventions, comorbidities of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
337
3
28

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 403 publications
(437 citation statements)
references
References 400 publications
13
337
3
28
Order By: Relevance
“…These variations in the incidence of ROP may reflect differences in study populations, mortality rates, and characteristics of neonatal care in each institution, corroborating the need to further investigate the risk factors for the development of ROP. Numerous published case series have shown that infants with ROP in low- and middle-income nations have higher average BW and GA than infants with ROP in the United States [ 20 ]. Most studies report ROP incidences of about 60% for babies with less than 1500 g in nurseries of high-income countries [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variations in the incidence of ROP may reflect differences in study populations, mortality rates, and characteristics of neonatal care in each institution, corroborating the need to further investigate the risk factors for the development of ROP. Numerous published case series have shown that infants with ROP in low- and middle-income nations have higher average BW and GA than infants with ROP in the United States [ 20 ]. Most studies report ROP incidences of about 60% for babies with less than 1500 g in nurseries of high-income countries [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy of prematurity (ROP) is the most common form of infant blindness worldwide, accounting for 150,000 blind children annually (1). Survival after premature birth requires oxygen supplementation that is paradoxically associated with toxicity to premature developing tissues, such as the lung alveoli, nephrons of the kidney, cerebral cortex, and retinal capillaries (2).…”
Section: Introductionmentioning
confidence: 99%
“…We found several factors were associated with treatment of ROP, including low birth weight, extreme premature birth, [19][20][21] exposure to higher levels of oxygen support, 22 and nosocomial sepsis. 23 We also identified exposure to erythropoietin alfa 21,24,25 and/or postnatal steroids 21,26 and severe apnea 27 as potential important factors promoting ROP disease progression. In addition, there are important comorbidities seen in infants who are treated for ROP.…”
Section: Discussionmentioning
confidence: 88%